2019
DOI: 10.1038/s41598-019-53233-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Wettability on the Response of a Quartz Crystal Microbalance Loaded with a Sessile Droplet

Abstract: In this work, the interaction between a sessile droplet’s contact angle and a quartz crystal microbalance (QCM) is elucidated. We differentiate the QCM’s frequency response to changes in the droplet contact area from variations in the dynamic contact angle. This is done by developing a computational model that couples the electrical and mechanical analysis of the quartz substrate with the visco-acoustic behavior of the sessile droplet. From our analysis, we conclude that changes in the contact angle have an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The evaporation process of the sessile droplets was measured using a quartz crystal microbalance (Figure b) that is highly sensitive to changes in the temporal droplet radius. , We observed that the droplet evaporating on the planar surface (without cellulose coating) initially followed a constant contact radius (CCR) regime, during which the liquid–solid contact line was pinned while the contact angle and the droplet height decreased as the evaporation continued followed by a depinning period where the contact line contracted until the evaporation was completed. In contrast, for the substrate covered by the cellulose thin film, the droplet remained evaporating in a constant contact radius mode for most of its lifetime due to the capillary-driven spreading and imbibition in the presence of the porous medium, leading to a much accelerated evaporation process .…”
Section: Resultsmentioning
confidence: 99%
“…The evaporation process of the sessile droplets was measured using a quartz crystal microbalance (Figure b) that is highly sensitive to changes in the temporal droplet radius. , We observed that the droplet evaporating on the planar surface (without cellulose coating) initially followed a constant contact radius (CCR) regime, during which the liquid–solid contact line was pinned while the contact angle and the droplet height decreased as the evaporation continued followed by a depinning period where the contact line contracted until the evaporation was completed. In contrast, for the substrate covered by the cellulose thin film, the droplet remained evaporating in a constant contact radius mode for most of its lifetime due to the capillary-driven spreading and imbibition in the presence of the porous medium, leading to a much accelerated evaporation process .…”
Section: Resultsmentioning
confidence: 99%
“…The success of hydrocarbon recovery from conventional and unconventional reservoirs depends on the affinity of the reservoir rock for the oil/water system (Agbalaka et al, 2008;Murray and Narayanan, 2019;Ahmadi et al, 2020;Alhammad et al, 2022;Rego et al, 2022;Yekeen et al, 2023). The foremost reason for treating the quartz surface with MB is to alter the wettability from hydrophobic to hydrophilic conditions and improve hydrocarbon recovery from the matured reservoirs (Zhang et al, 2007;Kamal et al, 2017;Li et al, 2018a;Omran et al, 2020;Tackie-Otoo et al, 2022;Alhammad et al, 2023b).…”
Section: Resultsmentioning
confidence: 99%
“…Wettability and droplet evaporation plays an important role in nature, daily life, and many technological applications, manufacturing engineering, chemical and medical products. Understanding the interaction and wetting dynamic of droplets with various surfaces, and the complex mechanisms of drying processes is essential [1,2]. Moreover, the formation of drying defects and watermarks (WM), after the wet cleaning procedures in the semiconductor industry, has been identified as a serious problem [3].…”
Section: Background Motivation and Objectivementioning
confidence: 99%